2018
DOI: 10.3390/jimaging4010024
|View full text |Cite
|
Sign up to set email alerts
|

Stable Image Registration for In-Vivo Fetoscopic Panorama Reconstruction

Abstract: Abstract:A Twin-to-Twin Transfusion Syndrome (TTTS) is a condition that occurs in about 10% of pregnancies involving monochorionic twins. This complication can be treated with fetoscopic laser coagulation. The procedure could greatly benefit from panorama reconstruction to gain an overview of the placenta. In previous work we investigated which steps could improve the reconstruction performance for an in-vivo setting. In this work we improved this registration by proposing a stable region detection method as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…The proposed approach may also be integrated with recent work, which deals with vessel segmentation from placenta images 1,34 , stitching of fetoscopy images to build placental panoramic image 12,44 and classification of TTTS surgical phases 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The proposed approach may also be integrated with recent work, which deals with vessel segmentation from placenta images 1,34 , stitching of fetoscopy images to build placental panoramic image 12,44 and classification of TTTS surgical phases 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Such feature descriptors are attractive initial options for mosaicking algorithms, as they are easy to describe mathematically and do not require application-specific training datasets. They have poor repeatability when applied to fetoscopic video frames, however, which makes it difficult to consistently extract enough frame-to-frame correspondences to estimate the motion of the fetoscope [13]. Deep-learned vessel segmentations have the potential to be invariant to many of the visual distractors present in fetoscopic video frames and therefore have the potential to serve as more robust and more repeatable features for panorama construction.…”
Section: Discussionmentioning
confidence: 99%
“…Gaisser et al [13], for example, simulated ex vivo and in vivo settings using a placental phantom and found that the performance of various feature detection algorithms could fall dramatically in the translation to in vivo. A feature detector could detect as many as 73% fewer features in images acquired in vivo settings as opposed to images acquired in ex vivo settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method generates noticeable results (back projection error of 0.6 pixel), but cannot be applied to real time tracking: it needs 3.4sec for every pair of images. In [12], the authors apply a novel approach based on the use of convolutional neural networks, with the need of a first learning phase. The used images come from a simulated placenta, with better visual conditions than in real scenarios.…”
Section: Related Workmentioning
confidence: 99%